Open Trips to the Baduy Tribe as an Alternative Tourism Trend Among Young People - Setyawati, Barliani Dewi; Sopyan, Adi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The growing popularity of open trip packages—group travels that bring together individuals who may not know each other beforehand—has become a noticeable trend among young travellers in Indonesia. One of the destinations that frequently appears in these travel programmes is the Baduy region in Banten, an area known for its strong cultural traditions and limited interaction with modern influences. This study explores the reasons young people choose to join open trips to Baduy, how they view the local culture, and what kinds of social and cultural effects their visits may have. Using a qualitative approach that combines in-depth interviews, participatory observation, and online questionnaires, the research seeks to capture the experience of both visitors and the local community. The results show that many young travellers are driven by a need for genuine and meaningful experiences, a curiosity about indigenous culture, and a wish to step away from digital routines for a while. Although most participants express admiration for the values upheld by the Baduy people, several behaviours witnessed during the trips do not fully align with local expectations, raising concerns about cultural sensitivity. These findings point to the importance of providing proper guidance and information to open trip participants, so that visits to Baduy can take place in a way that respects local customs and supports the preservation of community life.